THE INFLUENCE OF STRATEGIC VISION ON PARTICIPATION IN GOOD GOVERNMENT GOVERNANCE - Jovan Febriantoko; Desi Indriasari; M.Sang Gumilar Panca Putra; Rio Marpen (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aimed to find out the influence of Strategic Vision on participation in good government governance of North Sumatra, West Sumatra, and South Sumatra Provinces during 2016 – 2018. Good government governance is very important if implemented in Indonesia because every country or province definitely really needs good government or often called Good Government Governance. Good governance is regulated in Law Number 17 of 2003 and Law Number 32 of 2004. Data were analyzed using SPSS (statistical product and service solution) version 26 on classical assumption test, regression analysis, and t-test. Based on the t-test results, Strategic Vision had no significant influence on participation in good government governance of North Sumatra, West Sumatra, and South Sumatra Provinces during 2016 – 2018. Therefore, in addition to a strong commitment, the government needs to adopt and use the right strategy in implementing the principles of Good Government Governance.